Perlindungan Hukum Terhadap Pelajar Yang Melanjutkan Studi Diluar Negeri - Sutarni Sutarni (Fakultas Hukum universitas Islam Sumatera Utara, 2021)
AbstrackLegal protection for Indonesian Students Abroad refers to the provisions of legal protection for Indonesian citizens abroad which are basically subject to the provisions of Indonesian national law and provisions of international law. Legal protection for students abroad is divided into two, namely protection during times of peace and during times of armed conflict, both national and international.Education is part of an effort to enable every human being to develop his / her potential in order to grow into a human being who is strong and has character and has a healthy social life. Education is always changing and developing progressively. The educational process carried out in an effort to educate the nation and develop the character of the nation to become more moral is what is called the national education system. In the 1945 Constitution, Legal protection for Indonesian students abroad refers to the protection of citizens abroad as stipulated in the Preambule of the 1945 Constitution and Article 28 G The 1945 Constitution, Law Number 12 of 2006 concerning Citizenship Republic of Indonesia, as well as Law Number 37 of 1999 concerning Foreign Relations. Indonesian students abroad, in addition to Indonesian Workers and Country Representatives Abroad, are a group that must receive full protection. Protection of citizens, especially students who are outside Indonesia includes: protection in a state of conflict or in a state of peace. Legal protection in times of war includes international armed conflicts and internal armed conflicts in accordance with the provisions of international humanitarian law which are mainly derived from the Geneva Convention and its Additional Protocol. Keywords: legal protection, international students, Geneva Convention ABSTRAKPerlindungan hukum Pelajar Indonesia di Luar Negeri merujuk pada ketentuan perlindungan hukum Warga Negara Indonesia di Luar Negeri yang pada dasarnya tunduk pada ketentuan hukum nasional Indonesia dan ketentuan hukum internasional. Perlindungan hukum pelajar di luar negeri sendiri dibagi menjadi dua, yakni perlindungan pada masa damai dan pada masa konflik bersenjata baik yang sifatnya nasional maupun internasional. Pendidikan adalah bagian dari upaya untuk memampukan setiap insan untuk mengembangkan potensi dirinya agar tumbuh menjadi manusia yang tangguh dan berkarakter serta berkehidupan sosial yang sehat. Pendidikan selalu berubah dan berkembang secara progresif. Proses pendidikan yang dilaksanakan dalam upaya mencerdaskan bangsa serta mengembangkan watak banggsa menjadi lebih bermoral, itulah yang disebuut sistem pendidikan nasional. Dalam UUD 1945, Perlindungan hukum pelajar Indonesia di luar negeri merujuk pada perlindungan warga negara di luar negeri yang tertuang di dalam Preambule Undang Undang Dasar 1945 serta Pasal 28 G Undang Undang Dasar 1945, Undang Undang Nomor 12 Tahun 2006 tentang Kewarganegaraan Republik Indonesia, serta Undang Undang Nomor 37 Tahun 1999 tentang Hubungan Luar Negeri. Pelajar Indonesia di luar negeri, disamping Tenaga Kerja Indonesia dan Perwakilan Negara di Luar Negeri, merupakan golongan yang harus mendapatkan perlindungan secara penuh. Perlindungan terhadap warga negara khususnya pelajar yang berada di luar Indonesia mencakup perlindungan dalam keadaan konflik maupun dalam keadaan damai. Perlindungan hukum di dalam masa perang mencakup konflik bersenjata internasional dan konflik bersenjata internal sesuai dengan ketentuan hukum humaniter internasional yang utamanya bersumber dari Geneva Convention dan Additional Protocolnya. Kata Kunci : perlindungan hukum, pelajar luar negeri, Geneva Convention